Corporate governance and operational risk disclosure: evidence from shariah-compliant companies in Malaysia / Nurhafiza Mohammad ... [et al.] - Mohammad, Nurhafiza; Ismail, Rina Fadhilah; Zainon, Saunah; Mohd Abdul Kadir, Juliana (Universiti Teknologi MARA, 2021)
This study aimed to examine the level of operational risk disclosure among Shariah-compliant companies in Malaysia. The relationship between corporate governance characteristics and operational risk disclosure was also examined by focusing on board characteristics, i.e. independent directors, audit committee meetings, Muslim directors, women directors and education levels of the directors. The sample comprised of 285 Shariah-compliant companies listed in the ACE Market of Bursa Malaysia for the financial years 2014 to 2018. The study used content analysis to assess operational risk disclosure. The information disclosure was scored using an adapted disclosure index. Findings revealed that the disclosure of operational risk information in Shariah-compliant companies was at a moderate level, specifically not more than sixty per cent. More importantly, the analysis showed a positive significant relationship between a woman director and operational risk disclosure. However, a negative significant relationship was found between Muslim directors and operational risk disclosure. Other independent variables were found to have no relationship with the operational risk disclosure. The findings may provide future researchers and regulators with references for assessing the level of operational risk disclosure among public listed companies in Malaysia and are expected to deliver some improvement in examining other characteristics to strengthen the governance practices in Malaysia.